Association of frequent genetic variants in platelet activation pathway genes with large-vessel ischemic stroke in Polish population. (2nd January 2017) - Postula, Marek; Janicki, Piotr K.; Milanowski, Lukasz; Pordzik, Justyna; Eyileten, Ceren; Karlinski, Michal; Wylezol, Pawel; Solarska, Marta; Czlonkowka, Anna; Kurkowska-Jastrzebka, Iwona; Sugino, Shigekazu; Imamura, Yuka; et al.
Abstract: Platelets are critically involved in the development of cerebral ischemia. Our study aimed to establish an association between frequent (minor allele frequency (MAF) > 5%) genetic polymorphisms in 84 candidate genetic loci previously linked to platelet reactivity by the use of next-generation sequencing of exons from pooled DNA samples in Polish patients with a history of large-vessel ischemic stroke. Genetic analysis was performed on blood samples obtained from 500 patients (diagnosed with acute non-cardioembolic ischemic stroke with coexisting large-artery atherosclerosis) and age/sex/history of smoking matching 500 controls of Polish origin with high risk of cardiovascular disease. Sequencing of 10 pools (five for each ischemic and control groups) was performed on the Ilumina HiSeq2500 sequencer which generated an average of 36.1 (22.7–45.9 range) million pair-end 101 bp reads and 5.3 (3–7 range) Gbp per pooled sample consisting of 100 subjects. In total, we observed 789 frequent polymorphisms in the sequenced 84 genes (703 of single-nucleotide polymorphism (SNP) type and 86 indels). When the MAF between control and stroke groups was compared, only two intronic polymorphisms (1 SNP and 1 indel) in RGS7 (rs127445 36) and ANKS1B (rs398098426) genes, respectively, show statistically significant differences, which persisted after individual genotyping of the variants and adjustment for potential confounding factors. From the remaining variants, 35 polymorphisms displayed various degrees of nominal significance (from 0.6.3 × 10 −5 to 5 × 10 −2 ) and 754 polymorphisms did not show any statistical significance when comparison was evaluated for differences in MAF between the study groups. In conclusion, the results of the study demonstrate statistically significant differences in two frequent intronic genetic variants (in RGS7 and ANKS1B ) that could be associated with the platelet function between ischemic stroke patients with coexisting large-vessel atherosclerosis and control patients having high vascular risk.